Hydrogen-Bonded Interfacial Super-Assembly of Spherical Carbon Superstructures for High-Performance Zinc Hybrid Capacitors - Qin, Yang; Hu, Chengmin; Huang, Qi; Lv, Yaokang; Song, Ziyang; Gan, Lihua; Liu, Mingxian (Nano-Micro Letters, 2025)
Carbon superstructures with multiscale hierarchies and functional attributes represent an appealing cathode candidate for zinc hybrid capacitors, but their tailor-made design to optimize the capacitive activity remains a confusing topic. Here we develop a hydrogen-bond-oriented interfacial super-assembly strategy to custom-tailor nanosheet-intertwined spherical carbon superstructures (SCSs) for Zn-ion storage with double-high capacitive activity and durability. Tetrachlorobenzoquinone (H-bond acceptor) and dimethylbenzidine (H-bond donator) can interact to form organic nanosheet modules, which are sequentially assembled, orientally compacted and densified into well-orchestrated superstructures through multiple H-bonds (N–H···O). Featured with rich surface-active heterodiatomic motifs, more exposed nanoporous channels, and successive charge migration paths, SCSs cathode promises high accessibility of built-in zincophilic sites and rapid ion diffusion with low energy barriers (3.3 Ω s−0.5). Consequently, the assembled Zn||SCSs capacitor harvests all-round improvement in Zn-ion storage metrics, including high energy density (166 Wh kg−1), high-rate performance (172 mAh g−1 at 20 A g−1), and long-lasting cycling lifespan (95.5% capacity retention after 500,000 cycles). An opposite charge-carrier storage mechanism is rationalized for SCSs cathode to maximize spatial capacitive charge storage, involving high-kinetics physical Zn2+/CF3SO3− adsorption and chemical Zn2+ redox with carbonyl/pyridine groups. This work gives insights into H-bond-guided interfacial super-assembly design of superstructural carbons toward advanced energy storage. Highlights: 1 The spherical carbon superstructures (SCS-6) are synthesized by a hydrogen-bonded interfacial super-assembly, owning surface-opening pores, interconnected channels and rich heteroatom species. 2 Maximized accessibility of surface-active sites and opposite charge-carrier storage mechanism ensure high ion storage efficiency. 3 The assembled zinc-ion hybrid capacitor based on SCS-6 delivers ultrahigh energy density (166 Wh kg−1) and super-stable cycle lifespan (500,000 cycles).